Income Risk Management in Agriculture using Financial Support - Novickytė, Lina (European Journal of Sustainable Development, 2018)
Agriculture is often characterized by high variability of production outcomes, agricultural commodities prices are extremely fluctuating, and segmented agricultural markets will be influenced mainly by local supply and demand conditions, while more globally integrated markets will be significantly affected by international production dynamics. Unexpected changes in agriculture policy that affect producers’ activities constitutes another important source of uncertainty to agricultural producers. Changes in regulations can have significant impact on the profitability of farming activities. Individual farms have different strategies and attitudes to manage the income risk. This article presents some theoretical insights on risks in agriculture, risk management strategies and the impact of financial support to manage risk. Government and other public stakeholders participate in risk management based on the economic benefits that farmers due to ineffective risk management and the inability of the market itself to neutralize the negative effects of the risk receive lower income. Then public stakeholders try to remedy market imperfections using various forms financial support or compensation mechanism. This strategy is often criticized, as it is impeding the functioning of free market and distorting the behaviour of farm managers in terms of risk tolerance. Therefore, the purpose of this article is to present the state-of-play in agriculture risk management and how agricultural producer’s behaviour and risk tolerance affect their risk perception and the choice of different risk management strategies. The results of the review are useful in assessing the effectiveness of the current Common Agricultural Policy and considering the obtained results to draw up strategic guidelines for the future Common Agricultural Policy. Keywords: agriculture, agricultural policy, financial support, income risk, risk perception, behaviour.